DIGITAL SCIENCE COMIC AND ITS INFLUENCE TOWARDS STUDENTS' UNDERSTANDING OF HUMAN DIGESTIVE SYSTEM TOPIC - Kusmarani, Fauzia Maulidiastuti (2016)
This research aims to investigate how the use of digital science comic as a learning aid influences students' understanding of human digestive system topic in junior high school level as compared to conventional teaching media. Prior to research, a series of digital comic strips depicting human digestive system was developed and sent to experts for judgment and critiquing. The comics were then used as an instrument in this research, which employed quasi experiment method with pretest-posttest comparison design. Two groups of participants, each consisting of 37 subjects, were selected from eighth grade junior high school students. One group was designated as the experiment group which used the digital science comic as learning aid; while the other group took part as the control group which used conventional teaching media. Participants were required to complete a set of pretest and posttest. Analysis of the normalized gains of both groups using Mann-Whitney U test revealed asymptotic sig. score below 0.05; proving that there are significant differences between the knowledge improvements of both groups. In conclusion, using digital science comic as a learning aid gives positive improvement towards students' understanding of the topic; however, there are certain limitations of how much information can be give in the science comics. Thus, digital science comics are best used as a learning aid for subject materials which require lower order thinking as described in Revised Bloom's Taxonomy.